Efficient Quantification of Free and Forced Convection. Issue 1 (17th December 2018) - Glänzel, Janine; Stoll, Martin; Unger, Roman
Abstract: Thermo‐elastic deformations represent one of the main reasons for positioning errors in machine tools. Investigations of the thermo‐mechanical behaviour of machine tools often rely on accurate simulations involving large‐scale CFD simulations, where the heat transfer coefficient is computed. It has been shown that radial basis functions (RBFs) are a valid tool to reduce the number of CFD simulations by interpolation. We here present an efficient approach for the case of a three‐axis milling machine.